Determination of the Degree of Consumption (DoC) of Lube Engine Oils Using Fluorescence Spectroscopy - Abdul Kareem, Rawnaq Qahtan; Al-Janabi, Khalid W. Salih (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The accreditation of a fast, inexpensive, and simple way to discriminate between different kinds of oils and their efficacy â€œdegree of consumption (DoC)â€ has been developed. The fluorescence spectroscopy provides a reliable method for oil inspection without resorting to tedious separation. Different new and used oil samples available in the local Iraqi market were investigated. While the challenge is to build a directory containing data of all the oils available in the local market. This method expected to control the falsified (forged) trademarks of motor oils and to discriminate between different oils. The excitation-emission spectra of oil samples were determined in the range of 200 â€“ 600 nm. The effect of the presence of trace metals on the ï¬‚uorescence intensity of oils was considered by adding few milligrams of (Cu, Al, Fe) to the diluted oil solution. No major effect noticed on ï¬‚uorescence intensity. The research suggests installing a simple Spectrofluorometer into vehicles to check the DoC of the oil regularly and to notify the driver exactly when to replace the engine oil. The obtained results indicate the applicability to execute such gadget to be installed in the vehicles for routine detection of the engine oil quality and its degree of consumption DoC. As well as demonstrate the potential of the technique in oil identification and could be further developed.